Exogenous Linoleic Acid Intervention Alters Hepatic Glucose Metabolism in an Avian Embryo Model - Zhang, Xiufen; Wu, Qilin; Zheng, Wenxuan; Liu, Chuang; Huang, Liang; Zuo, Xin; Xiao, Wenquan; Han, Xiaofeng; Ye, Hui; Wang, Wence; Zhu, Yongwen; Yang, Lin (Frontiers in Physiology, 2022)
In the present study, developmental changes of gluconeogenesis and glycolysis in an avian model were measured, and then the intervention effects of in ovo feeding (IOF) linoleic acid (LA) on hepatic glucose metabolism were evaluated. In Exp.1, thirty fertilized eggs were sampled on embryonic days (E) of 16, 19, 22, 25, 28, 31, and thirty newly-hatched ducklings at hatch (E34 - E35). In Exp.2, a total of 120 fertilized eggs (60 eggs for each group) were injected into the yolk sac with PBS as the control group and LA as the IOF LA group on E25. Twelve eggs were selected for sample collection on E28 and E31. Serum contents of glucose, pyruvate, and lactate increased (P < 0.05) linearly or quadratically from E16 to hatch, as well as hepatic glycogen and pyruvate contents. Hepatic mRNA expression related to energy homeostasis, gluconeogenesis, and glycolysis increased (P < 0.05) in embryogenesis, and the plateau period was presented on E25 - E31. IOF LA decreased (P < 0.05) serum contents of glucose, triacylglycerol, cholesterol, and hepatic oleic acid, unsaturated fatty acids on E28, as well as the gene expression relative to gluconeogenesis. IOF LA increased (P < 0.05) pyruvate content in serum and liver, and hepatic gene expression relative to glycolysis on E31. In summary, hepatic gluconeogenesis and glycolysis were enhanced to meet the increasing energy demands of embryonic development during E25 - hatch. Exogenous LA intervention on E25 could inhibit hepatic gluconeogenesis and enhance glycolysis during the later developmental period, disrupting glucose embryonic homeostasis and energy status.